Increased Risk of Sexual Dysfunction in Male Patients with Psoriasis: A Nationwide Population‐Based Follow‐Up Study. (21st May 2012) - Chen, Yi‐Ju; Chen, Chih‐Chiang; Lin, Ming‐Wei; Chen, Tzeng‐Ji; Li, Cheng‐Yuan; Hwang, Chian‐Yaw; Chu, Szu‐Ying; Lee, Ding‐Dar; Chang, Yun‐Ting; Wang, Wen‐Jen; Liu, Han‐Nan
ABSTRACT: Introduction. An association between psoriasis and sexual dysfunction (SD) has been explored. However, the risk of SD after the diagnosis of psoriasis relative to the age‐matched general population remains unknown. Aim. To clarify the risk of developing SD in male patients with psoriasis. Methods. From 2000 to 2001, we identified 12, 300 male patients with newly diagnosed psoriasis and 61, 500 matching controls from National Health Insurance Database in Taiwan. Main Outcome Measures. The two cohorts were followed up until 2008, and we observed the occurrence of SD by registry of SD diagnosis in the database. Stratified Cox proportional hazard regressions were used to calculate the 7‐year SD risk for these two groups. Results. Of the 73, 800 sampled patients, 1, 812 patients (2.46%) experienced SD during the 7‐year follow‐up period, including 373 (3.03% of patients with psoriasis) in the study group and 1, 439 (2.34% of patients without psoriasis) in the comparison group. The hazard ratio (HR) for SD for patients with psoriasis was 1.27 times (95% confidence interval [CI], 1.11–1.46; P = 0.001) as high as that for patients without psoriasis after adjusting for age, monthly income, number of health‐care visits, systemic treatment, and other comorbidities. Stratified analysis showed that the risk of SD was higher in patients older than 60 years old (HR: 1.42, 95% CI: 1.12–1.81) and patients with psoriatic arthritis (HR: 1.78, 95% CI: 1.08–2.91). However, the risk of SD was not significantly elevated in patients receiving systemic treatment, including retinoid, methotrexate, and cyclosporine. Conclusions. Male patients with psoriasis are at increased risk of developing SD. Physicians should pay attention to the impact of psoriasis on psychosocial and sexual health, especially in old‐aged patients.